Perlindungan Hak Atas Penggantian Tempat Tinggal Warga Terdampak Penggusuran Kampung Bayam Menurut Perspektif Hak Ekosob - Putri, Syifadilla Subagyo; Prananda, Mayang Talentasari; Masdiana, Ismail; Wahyuni, Ridha (Media Hukum Indonesia (MHI), 2024)
The Law on Human Rights can generally be understood as provisions that protect human freedoms in sustaining their lives, including obtaining suitable housing, especially in preserving what has been theirs from the beginning. In the case of the eviction of settlements in the Kampung Bayam area, legal protection of human rights has not yet been realized to this day. The eviction carried out by the Jakarta Provincial Government was arbitrary, without considering its impact on residents who lost their homes and also as a form of deprivation of the economic, social, cultural rights of the Kampung Bayam community. Furthermore, until now, there has been no apparent effort from the government to restore the housing rights of the residents of Kampung Bayam. Moreover, Indonesia is a country based on the rule of law, which means Indonesia should prioritize the protection and respect of human rights as its main focus.